Gendered perspectives of trees on farms in Nicaragua: Considerations for agroforestry, coffee cultivation, and climate change - Gumucio, Tatiana; Twyman, Jennifer; Clavijo, Mónica (International Center for Tropical Agriculture, 2017)
Due to gender-specific roles and responsibilities, men and women face varying challenges and opportunities to mitigate and adapt to climate change impacts. It is particularly important to take into account the ways that men and women engage with tree resources in order to develop both equitable and effective interventions and strategies, recognizing that agroforestry is an important element of these. For instance, agroforestry is often included among the recommended climate-smart agricultural practices for high value tree crops, like coffee. The paper analyzes household level socioeconomic data collected in 2015 within a Climate-Smart Village of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in Tuma La Dalia, Nicaragua, where smallholder shade coffee production is a substantial economic activity. The area is also part of a Landscape Observatory of the CGIAR Research Program in Forests, Trees and Agroforestry (FTA). The survey instrument developed is based on the Women’s Empowerment in Agriculture Index (WEIA). From 271 households, a total of 493 surveys were carried out with adult men and women primary decision-makers. The intra-household survey collected data related to agricultural and agroforestry activities, and sex-disaggregated data on decision-making. The report provides initial insights into the uses and importance that women and men associate with trees on farms, as well as their participation in decision-making on agroforestry activities, in order to support the development of gender-sensitive climate change interventions focused on high value tree crops. In particular, findings suggest that women associate a greater number of household uses with on-farm trees than men. Furthermore, women may be more prone to give importance to fruit trees in comparison to men. Results also demonstrate differences in women’s and men’s perceptions of decision-making processes concerning trees on farms: women recognize their participation more than men, particularly when it concerns fruit trees and planting, as opposed to tree management.